And the winners are ... - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Watched by CTA staff and visitors, and flanked by Spore project officer Sam Matsangaise on his left, and, on his right, Helen Oguli and the Spore consortium s lead editor Paul Osborn, Carl B Greenidge holds up the winning entryBy 1 February 2002,...